EFFECT OF DIFFERENCES IN LIGHT INTENSITY ON ZOOXANTHELLA ABUNDANCE ON ACROPORA SP CORAL IN KASIAK ISLAND WATERS, WEST SUMATRA PROVINCE - Jean Novia Ain; Thamrin Thamrin; Musrifin Galib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Zooxanthella which acts as endosymbionts in corals requires optimal light for photosynthesis. This research was conducted in February 2019 which took place in the waters of the Kasiak Island of West Sumatra. Samples were analyzed at the Laboratory of Marine Biology, Faculty of Fisheries and Marine, University of Riau. This study aims to determine the abundance of zooxanthella and the effect of differences in light intensity on the abundance of zooxanthella on Acropora sp.. So the information is obtained about the optimal light intensity on the abundance of zooxanthella. Based on the results of observation, the abundance of zooxanthella in Acropora sp coral decreased with decreasing light intensity, so it can be seen that there was an effect of the difference in light intensity on the abundance of zooxanthella on Acropora sp. The abundance of zooxanthella in control (light intensity 60-93 μE/m2s) is 8.282.997 cells/cm2, in treatment 1 (light intensity 58 μE/m2s) amounting to 3.460.841 cells/cm2, in treatment 2 (light intensity 26 μE/m2s) of 2.113.296 cells/cm2, and in treatment 3 (light intensity 0 μE/m2s) of 588.065 cells/cm2. It was also found that the description of Acropora sp. Coral transplant business will be more optimally performed on the light intensity of 60-93 μE/m2s. Keywords:Zooxanthella, Acropora sp, Light Intencity